Multidisciplinary Collaborative Teaching Approach in Health Sciences Programs at Historically Black Colleges and Universities. - EDWARDS, JR., DOTHEL W.; JACKSON, VERONICA; RAINES, GRESHUNDRIA M.; HENDERSON, DEANNA L.; EDWARDS, YOLANDA V. (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
Practicing health sciences professionals may feel insufficiently trained in such critical areas as coping with diversity, working in teams, practicing prevention, and effectively using community resources. The goal of multidisciplinary collaborative teaching is to expose students early to other disciplines in the rehabilitation process. In most rehabilitation facilities, a multidisciplinary team of professionals works together to offer optimal patient/consumer care that yields optimal outcomes. This article provides health sciences educators with a conceptual overview of the importance of multidisciplinary collaborative teaching and its potential benefits for admissions, academic curricula, clinical internship placement, and employment.